Upaya meningkatkan hasil belajar dengan menggunakan media dan bahan kubus Styrofoam satuan mata pelajaran matematika kelas IV Sekolah Dasar - Emi, Sri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
In essence, education is a conscious effort by one person towards others in order to have recognition and skills. How to motivate students to better master the concept of learning objectives that are planned. In the process of education it always happens. Changes in behavior, not only changes from not knowing to knowing, but more than that, changes are expected to cover all aspects of education such as cognitive, effective and psychometric. This study aims to improve learning achievement of adding mixed fractions with unit cube media from Styrofoam students in class V SDN Kawengen 02 in 2018/2019 academic year. This research is a class action research carried out in two cycles with research subjects in class V SDN Kawengen 02 totaling 37 students. The instruments used in this study include the Student Task Sheet (LTPD), the student activity observation sheet, field notes and documentation drawings. Data from these instruments were analyzed using guidelines and established criteria. The results of the study show that learning using manipulative media can increase the active participation of students in learning which results in an increase in the achievement of learning outcomes.